Peningkatan Hasil Belajar Bahasa Inggris Materi Introduction melalui Model Problem Based Learning pada Siswa Kelas VII SMP - Andi Febryna; Rahmadian Rahmadian (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The primary objective of this research is to enhance English academic proficiency among seventh-grade pupils at UPT SMP Negeri 4 Takalar, specifically regarding